Implementasi Algoritma Galil Seiferas Pada Aplikasi Kebudayaan Indonesia Berbasis Android - Dewi Yuliati (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Culture is a whole system of ideas, actions, and results of human work in the context of community life owned by humans by learning. Indonesia has a variety of cultures. Indonesian culture is spread in many regions. Spread in 33 provinces in Indonesia with a variety of characteristics and characteristics that have regional values ​​that are packaged in various forms. The types of culture include: traditional houses, traditional clothing, traditional dances, traditional weapons, traditional musical instruments, and ethnic groups. Lack of knowledge of Indonesian culture in young people today tends to make people forget the culture itself. Therefore applications are needed that make it easier to find Indonesian culture. This mobile-based application was designed using the Galil Seiferas algorithm in searching Indonesian cultural applications. In the Galil Seiferas algorithm the search phase is carried out from the left to the right by initializing starting from the first index to the last index of the pattern. The solution drawn from this problem is by designing an Android-based Indonesian culture application that can be easily accessed and understood by the public, especially young people. However, due to the limitations of the smartphone screen to present information on Indonesian culture, string matching is needed to search for Indonesian culture. String matching algorithm is a string matching algorithm that is looking for a string consisting of several patterns (characters) in a large amount of text. For android-based Indonesian culture applications are designed using Seiferas galil algorithm.